2023
DOI: 10.1021/acsbiomaterials.3c00385
|View full text |Cite
|
Sign up to set email alerts
|

Sandblasted/Acid-Etched Titanium Surface Modified with Calcium Phytate Enhances Bone Regeneration in a High-Glucose Microenvironment by Regulating Reactive Oxygen Species and Cell Senescence

Abstract: Hyperglycemia in patients with diabetes affect osteoblast function, leading to abnormal bone metabolism and implant failure. Adequate bone volume surrounding an implant is essential for osseointegration, which can be improved by implant surface modifications. In this study, titanium surfaces were hydrothermally treated with a mixture of phytic acid (PA) and calcium hydroxide to produce a calcium-decorated surface. The control group comprised pure titanium with a sandblasted/acid-etched (SLA) surface. The eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…According to Dong et al [43], osteointegration can be improved by modifying the implant surface. In the study, a titanium surface was enhanced with a mixture of phytic acid and calcium hydroxide.…”
Section: Discussionmentioning
confidence: 99%
“…According to Dong et al [43], osteointegration can be improved by modifying the implant surface. In the study, a titanium surface was enhanced with a mixture of phytic acid and calcium hydroxide.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical investigations revealed a higher incidence of early implant failure compared with late failure in diabetic patients and increased the risk of peri-implantitis, a crucial factor in the overall success of dental implants with 5% of patients experiencing implant failure due to implantitis (Chrcanovic et al 2014). While direct evidence establishing a link between poor metabolic control, hyperglycemia, and implant failure remains limited, the strategies using surface modifications to improve implant success have been a focus; for example, sandblasted/acid-etched titanium surface modified with calcium phytate is a candidate for improving implant osseointegration (Dong et al 2023). Even though it is unusual to treat patients with poor hyperglycemic control, insights from preclinical studies can shed light to more options when considering implant therapy for diabetic patients.…”
Section: Animal Models Of T2dmmentioning
confidence: 99%
“…During the processes of bone healing after trauma (such as TES), HBMSCs are recruited from bone marrow to the damaged area and differentiate into osteoblasts, leading to the secretion, synthesis, and mineralization of bone matrix . It has been demonstrated that accumulated ROS disrupted the osteogenic differentiation of HBMSCs, resulting in compromised bone metabolism and impaired bone regeneration . In addition, bone is composed of highly vascularized tissue, and these blood vessels play important roles in bone remodeling .…”
Section: Introductionmentioning
confidence: 99%
“…21 It has been demonstrated that accumulated ROS disrupted the osteogenic differentiation of HBMSCs, resulting in compromised bone metabolism and impaired bone regeneration. 22 In addition, bone is composed of highly vascularized tissue, and these blood vessels play important roles in bone remodeling. 23 HUVECs compose the blood vessels and secrete several angiogenesis factors.…”
Section: ■ Introductionmentioning
confidence: 99%